GENRE CERITA SILAT DALAM SASTRA INDONESIA - Susanto, Dwi (Diksi, 2009)
There are several genres in literature such as mystery, detective, gothic, and crimegenres. Something unique in Indonesian literature is the martial art story genre, which maynot be found in other countries' literature, especially in western literature. From itsformula, such a genre can be part of the world literature because it emphasizes the pluralityand the acceptance of other cultures. This article briefly describes the development of themartial art story genre in Indonesia, consisting of two parts, namely the genre as a productand a process of reception of Chinese literature through Chinese descendants and the genredeveloped from indigenous traditional stories in Indonesia. Although such a division is stilldebatable, this article describes the development from those two processes.Keywords: martial art story, reception of Chinese literature, Indonesian tradition